Effects of Labrador Tea, Peppermint, and Winter Savory Essential Oils on Fusobacterium nucleatum - Amel Ben Lagha; Katy Vaillancourt; Patricia Maquera Huacho; Daniel Grenier (MDPI AG, 2020)
Bad breath or halitosis is an oral condition caused by volatile sulfur compounds (VSC) produced by bacteria found in the dental and tongue biofilms. Fusobacterium nucleatum is a Gram-negative anaerobic bacterium that has been strongly associated with halitosis. In this study, essential oils (EO) from three plants, Labrador tea (Rhododendron groenlandicum [Oeder] Kron & Judd), peppermint (Mentha x piperita L.), and winter savory (Satureja montana L.), were investigated for their effects on growth, biofilm formation and killing, and VSC production by F. nucleatum. Moreover, their biocompatibility with oral keratinocytes was investigated. Using a broth microdilution assay, winter savory EO and to a lesser extent Labrador tea and peppermint EO showed antibacterial activity against F. nucleatum. A treatment of pre-formed biofilms of F. nucleatum with EO also significantly decreased bacterial viability as determined by a luminescence assay monitoring adenosine triphosphate production. The EO were found to permeabilize the bacterial cell membrane, suggesting that it represents the target of the tested EO. The three EO under investigation were able to dose-dependently reduce VSC production by F. nucleatum. Lastly, no significant loss of cell viability was observed when oral keratinocytes were treated with the EO at concentrations effective against F. nucleatum. This study supports the potential of Labrador tea, peppermint, and winter savory EO as promising agents to control halitosis and promote oral health.